To screen or not to screen? Critical reflections on the use of mental health screening in high-performance sport - Kegelaers, J.; Wylleman, P.; Brevers, D.; Pankow, K.; Kenttä, G. (Psychology of Sport and Exercise, 2026)
Mental health screening has rapidly gained prominence within sport organisations as an important mental health initiative, to identify individuals at risk and facilitate early intervention. Despite growing policy endorsement and institutional uptake, the empirical and ethical foundations underpinning mental health screening in sport have received limited critical scrutiny. The present paper, therefore, provides a critical narrative review to examine the conceptual, empirical, and ethical foundations of mental health screening in sport. We first provide a concise overview of what is meant by mental health screening in the context of high-performance sport, followed by a discussion of the rationale behind its use. We then critically examine the available evidence, structured around four key areas: (a) the predictive validity of existing screening instruments, (b) implementation and feasibility considerations, (c) the effectiveness of mental health screening programmes, and (d) potential harms and unintended consequences associated with screening. We conclude the paper by offering our recommendations on the conditions under which mental health screening may be considered, as well as situations in which alternative approaches may be more appropriate.